GLOBAL TRENDS IN TEACHER PERFORMANCE ASSESSMENT: BIBLIOMETRIC ANALYSIS TO IDENTIFY BEST PRACTICES ON SCOPUS DATABASE - Insan, Abdul; Sudirman; Untung Waluyo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2025)
This study aims to explore global trends and best practices in teacher performance assessment through bibliometric analysis. Using the Scopus database and the Biblioshiny tool, the research identifies key contributions, themes, and collaborations within the field. The analysis focuses on research performance, including annual scientific production, relevant sources, authors, affiliations, and countries, as well as science mapping to examine co-occurrence networks, three-field plots, collaboration networks, and world maps. Results indicate a significant increase in publications from 2018 to 2024, reflecting growing global interest in improving educational quality through teacher performance assessment. Collaboration networks highlight six distinct thematic clusters, while the world map underscores the pivotal role of international partnerships in advancing innovative and evidence-based practices. These findings emphasize the importance of research-driven approaches in enhancing teacher effectiveness and fostering global educational development.